Variability of heart beat frequency in different body positions and during MASR in a person with lower member unilateral amputation - Silva, Andréa Lúcia Gonçalves da (2019)
Amputation causes decrease of mobility and physical activities, affecting the muscle-skeleton, respiratory and cardiovascular systems. Variability of heart frequency (VFC) at different body positions and during Respiratory Sinus Arrhythmia (RSA) was analyzed in people with amputation of unilateral lower members with prosthesis (MMII). Current transversal study, with convenience sample, evaluated seven males with trauma-caused amputations. Clinical variations and VFC were registered with regard to supine position, orthostasis, sedestation (10 min) and during RSA (4 min). The subjects at rest showed a predominance in increasing sympathetic modulation as the orthostatic position is achieved (p =